Electronic structure and ionization energies of palladium and platinum N-heterocyclic carbene complexes. - Green, J; Herbert, B (2005)
Density functional methods have been used to calculate the geometries, electronic structure and ionization energies (IE) of N-heterocyclic carbene complexes of palladium and platinum, [M(CN2R2C2H2)2](M = Pd, Pt; R = H, Me, Bu t). Agreement with X-ray structures (R = Bu t) was good. Calculated IE agreed well with the photoelectron (PE) spectra (R = Bu t); metal bands were calculated to be within 0.25 eV of the experimental values, whereas the higher lying ligand bands deviated by up to 0.9 eV. Spin-orbit methods were needed to achieve this level of agreement for the Pt complex, but the calculations were found to underestimate the spin-orbit splitting somewhat. The principal metal-ligand bonding is between the carbene lone pair HOMO and a (d(z2)+ s) hybrid on the metal. The metal p(z) orbital contributes very little to the bonding. The metal d(xz,yz) orbitals mix primarily with the filled pi3 orbitals on the ligands and secondarily with the empty pi5 orbitals. Consequently they are little stabilized in comparison to the metal d(xy,x2- y2) orbitals, which are non-bonding in the complex. The first PE band for both the Pd and Pt complexes is from ionization of a (s - d(z2)) hybrid orbital. The IE is greater for Pt than for Pd on account of the post-lanthanide relativistic stabilization of the Pt 6s orbital.